Comparing the effects of ethanol, Betadine, and ethanol-chlorhexidine gluconate on phlebitis induced by peripheral intravenous catheters - Shole Shami; Mohammad Fathi; Dowlat Mohammadi (Kurdistan University of Medical Sciences, 2015)
Background and aim: Phlebitis and infection at the insertion site are among the most prevalent complications of peripheral intravenous catheters. The type of topical antiseptic solution used for preparing the catheter insertion site can affect the rate and the severity of these complications. The aim of this study was to compare the effects of ethanol, Betadine, and ethanol-chlorhexidine gluconate combination on phlebitis induced by peripheral intravenous catheters. Methods: In this clinical trial, 123 patients were selected from the medical care wards of Besat Hospital, Sanandaj, Iran. Patients were randomly allocated to the ethanol, Betadine, and ethanol-chlorhexidine gluconate groups. In these three groups, the catheter insertion site was scrubbed by using 70% ethanol, 10% Betadine, or 35% ethanol-2% chlorhexidine gluconate, respectively. The rate and the severity of phlebitis and local infection were assessed by using a four-point scale. Study data were analyzed by conducting the one-way analysis of variance and the t tests by using the SPSS software. Findings: Study groups did not differ significantly from each other regarding variables such as age, gender, catheter size, and the catheter insertion site. The rates of phlebitis in the ethanol, Betadine, or ethanol-chlorhexidine gluconate groups were respectively equal to %46, %53, and %22. In total, three patients developed local infection at the catheter insertion site, all of whom were from the Betadine group. Conclusion: Compared with 70% ethanol and 10% Betadine solutions, 35% ethanol-2% chlorhexidine gluconate combination is more effective in preventing phlebitis and local infection at the insertion site of peripheral intravenous catheters.